FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA IBU RUMAH TANGGA DI WILAYAH KERJA PUSKESMAS PETALING KECAMATAN MENDO BARAT KABUPATEN BANGKA - Misyati S Asmaruddin (Program Studi Ilmu Kesehatan STIKES Abdi Nusa Pangkalpinang, 2022)
PHBS in the household is an effort to empower household members to know, be willing and able to carry out clean and healthy living behaviors and play an active role in the health movement in the community. Based on data from the Petaling Health Center, the PHBS coverage in the Petaling Health Center work area in 2019 was 69.87%, in 2020 it decreased by 51.82% and in 2021 it increased by 60.76%. This study aims to determine the factors that influence the application of Clean and Healthy Living Behavior (PHBS) to housewives in the working area of ​​Petaling Health Center, Mendo Barat District, Bangka Regency in 2022. The type of research used in this research is analytic with survey method and cross sectional study approach. This research was conducted in the working area of ​​the Petaling Public Health Center, Mendo Barat District, Bangka Regency in August 2022. The population in this study were housewives in the working area of ​​the Petaling Health Center which amounted to 10,468 households, with a total sample of 109 respondents. Analysis of the data used includes univariate and bivariate analysis using the Chi Square test. The results showed that there was an influence of Knowledge (p=0.000, POR=13,789), Attitude (p=0.011, POR=3.508), Family Income (p=0.026, POR=6349), Infrastructure (p=0.000, POR= 27.491), Family Support (p=0.000, POR=12.364), and the Role of Health Officers (p=0.031, POR=0.262) on the implementation of PHBS in housewives. The key can be that infrastructure is the dominant factor influencing the application of clean and healthy living behavior (PHBS) to housewives. Health workers are expected to be extra and innovative in conducting counseling on clean and healthy living behavior (PHBS).